A framework for the successful implementation of food traceability systems in China. Issue 4 (8th August 2017) - Duan, Yanqing; Miao, Meiyin; Wang, Ruimei; Fu, Zetian; Xu, Mark
ABSTRACT: Implementation of food traceability systems in China faces many challenges due to the scale, diversity, and complexity of China's food supply chains. This study aims to identify critical success factors specific to the implementation of traceability systems in China. Twenty-seven critical success factors were identified in the literature. Interviews with managers at four food enterprises in a prestudy helped identify success criteria and five additional critical success factors. These critical success factors were tested through a survey of managers in 83 food companies. This study identifies six dimensions for critical success factors: laws, regulations, and standards; government support; consumer knowledge and support; effective management and communication; top management, company wide, and vendor support; and information and system quality.